Estudo por espalhamento Raman de efeitos anarmônicos e transição de fase do PbTiO3 : Sm3+ induzidos por pressão hidrostática e variação de temperatura - Machado, Marco Antonio Cunha (Universidade Federal de São Carlos, 2007)
In this work it was investigated, by using Raman spectroscopy, the effect of the substitucional disorder on the vibrational properties of the ferroelectric ceramics PbTiO3 doped with Samarium, at different temperatures and hydrostatic pressures. This material is interesting from the technological point of view because it is a combination between a material with intense ferroelectric properties and a rare earth ion, with very well known optical properties. From the academic point of view, the main purpose was to study qualitatively and quantitatively the combined chemical and structural effects on the phonon spectrum, which was achieved through measurements of the frequency shifts and broadenings of the vibrational modes, that is, the anharmonic effects. It was also investigated the changes in the Curie temperature, the critical transition pressure values and frequency pressure and temperature coefficients generated by substitucional disorder. A special attention was done to the behavior of the lower frequency mode, the so called soft mode, which plays an important role, whose frequency tends to zero with the approach of the ferroelectric-paraelectric transition. The Raman scattering, due to its sensitivity to short range order, to the character nondestructive, noninvasive is a technique well adapted to the purpose of the present study. The importance of the material and the choice of the technique are justified by the great number and quality of publications related to both in the international literature.
Keywords: Transição de fase; Efeitos anarmônicos; Raman, Espectroscopia de; Pressão hidrostática; Altas pressões; Cerâmicas ferroelétricas; CIENCIAS EXATAS E DA TERRA::FISICA